Core fucosylation of IL-2RB is required for natural killer cell homeostasis - Harrison Sudholz; Xiangpeng Meng; Hae-Young Park; Zihan Shen; Iva Nikolic; Joseph Cursons; Ethan D. Goddard-Borger; Iona S. Schuster; Christopher E. Andoniou; Mariapia A. Degli-Esposti; Nichollas E. Scott; Michael Chopin; et al. (Cell Reports)
Summary: Natural killer (NK) cell homeostasis and effector functions require context-dependent signaling via numerous receptors, including the interleukin-15 receptor (IL-15R). Post-translational modifications can regulate receptor signaling, impacting receptor turnover and trafficking. Core fucosylation is one such modification known to impact receptor expression and is uniquely mediated by fucosyltransferase 8 (FUT8). We identified FUT8 as an essential gene required for IL-15R responsiveness in a human NK cell genome-wide CRISPR screen. To further validate core fucosylation in IL-15R signaling and NK cell biology, mice lacking Fut8 in NK cells (Fut8fl/flNcr1cre/+) were generated. The loss of core fucose in murine NK cells resulted in severe NK cell lymphopenia, with a reduction in IL-15Rβ (IL-2RB/CD122) expression, impairing in vivo homeostatic proliferation. The loss of FUT8 also decreased NK cell cytotoxicity, tumor immunity, and early viral immunity. Taking these results together, we have identified FUT8 as a key modulator of NK cell biology by regulating their development, IL-15R expression, and signaling.